Fabrication of Tungsten & Tungsten Alloy and its High Heat Load Testing for Fusion Applications. (2016) - Kanpara, S.; Khirwadkar, S.; Belsare, S.; Bhope, K.; Swamy, R.; Patil, Y.; Mokariya, P.; Patel, N.; Patel, T.; Galodiya, K.
Abstract: Pure Tungsten (W) & Tungsten-lanthanum oxide (WL) were fabricated using Direct Sintering Press. W & WL found to be very good thermo-mechanical properties with higher densification desired for Plasma Facing Material. Both materials were subjected to transient high heat load conditions relevant to the ITER-like Divertor to study the material behavior using high heat flux test facility with electron beam heat source. Surface heat load of 1.0–3.14 MJ/m 2 energy density applied on W & WL with pulse duration of 20 ms. The crack formations and surface modification behaviors of material under high heat load were investigated with detailed characterization.